Association of total antioxidants level with glaucoma type and severity - Mousa, Ahmed; Kondkar, Altaf A.; Al-Obeidan, Saleh A.; Azad, Taif A.; Sultan, Tahira; Osman, Essam; Abu-Amero, Khaled K. (Saudi Medical Journal, 2015)
Objectives: To compare the mean total antioxidant status (TAS) among 3 glaucoma types, namely: pseudoexfoliation glaucoma (PEG), primary open angle glaucoma (POAG), and primary angle closure glaucoma (PACG), and study its potential association with various clinical glaucoma-parameters.Methods: In this case-control study, plasma samples were obtained between September 2013 and October 2014 from 340 glaucoma patients (PEG [n=54]; POAG [n=147]; PACG [n=139]), and 351 controls of matching age, gender, ethnicity, and 5 different systemic co-morbidities from King Abdulaziz University Hospital, Riyadh, Saudi Arabia. The TAS in all samples was determined by a colorimetric-based assay.Results: The mean±standard deviation of TAS was significantly lower among cases: 0.77±0.32 than controls: 1.1±0.22, p<0.0001. Moreover, the TAS levels were significantly different across the 3 types of glaucoma: 0.86±0.24 in PEG, 0.47±0.32 in POAG, and 0.98±0.41 in PACG (all p<0.0001). In addition, there was a significant correlation between TAS and age at onset (Pearson correlation coefficient [R] 0.17, p<0.0001), cup/disc ratio (R: -0.13, p=0.004), and number of anti-glaucoma medications (R: -0.16, p=0.001).Conclusion: Our findings provide evidence that plasma TAS levels are decreased in patients with glaucoma, more so in POAG and PEG than PACG, supporting the hypothesis that decreased antioxidative defense and/or increased oxidative stress may have a critical role in the pathogenesis of glaucoma.